Double Cerclage In Cervical Insufficiency: A Single Tertiary Center Experience - Hortu, Ismet; Sahin, Cagdas; Ilgen, Orkun; Kazandi, Mert; Akdemir, Ali; Ergenoglu, A. Mete (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: The aim of this study is to compare the perinatal outcomes of double cerclage via laparoscopic plus transvaginal technique in women with a history of transvaginal cerclage failure, between women with single transvaginal cerclage. Study Design: Five women who were diagnosed with cervical insufficiency with a history of at least one vaginal cerclage failure and 10 women who were diagnosed with cervical insufficiency were included in this study. Laparoscopic cerclage was performed to all women who have a medical history of vaginal cerclage failure, before pregnancy and additional transvaginal cervical cerclage was performed during their pregnancy (Group 1). Single transvaginal cervical cerclage was performed to the 10 women who had a short cervix and/or cervical insufficiency during their pregnancy (Group 2). The number of cerclage failure, perinatal outcomes, gestational week at the time of delivery, birth weight and Apgar scores were evaluated. Results: All five women in group 1 underwent a cesarean section. None of them had chorioamnionitis or poor obstetric outcomes and all gave birth after the 34th week of pregnancy. All ten women in group 2 were evaluated. Two women gave birth vaginally at the 33rd week of pregnancy. Remaining eight cases gave birth above 34th week of pregnancy. Six of the eight cases underwent cesarean section and two of the remaining were delivered vaginally. Mean birth weight of the fetuses were 2490±265 g and 2.710 ±361 g in group1 and group 2, respectively. Mean gestational age at the time of birth in group 1 and group 2 were found 36±1.83 weeks and 35.6±1.14 weeks, respectively. Conclusion: Laparoscopic cervical cerclage during pregnancy could be a safe and effective treatment. However, sometimes it might not be enough and transvaginal cervical cerclage may be needed to strengthen cervical tension.